Legal regulation of inheritance relations under martial law - V. P. Makovii; O. I. Yakymets; Z. I. Knysh (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the problems of legal regulation of inheritance relations under martial law. It has been analyzed the scientific works whose authors studied the peculiarities of legal regulation of inheritance relations under martial law. It is indicated that legal regulation of inheritance relations under martial law requires consideration of the following issues: 1) temporary restriction of constitutional rights and freedoms of human beings and citizens and rights and legitimate interests of legal entities due to the threat of restriction, with indication of the duration of such restrictions; 2) assistance in the exercise of civil rights and fulfillment of civil obligations by participants to such relations.